2016
DOI: 10.1038/srep27617
|View full text |Cite
|
Sign up to set email alerts
|

Values as determinant of meaning among patients with psychiatric disorders in the perspective of recovery

Abstract: Recovery is a personal process of growth that involves hope, self-identity, meaning in life and responsibility. Determinants of meaning have not been explored among populations of patients with persistent psychiatric conditions. However, an evidence-based approach aiming at assessing such determinants should provide some insight into the psychotherapeutic aspects of recovery. We tested a model hypothesizing that some symptoms and social parameters of patients are related to values, and secondarily to meaning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…epigenetic modifications, explain a part of the increased risk of depression of patients with child maltreatment history (Labonte et al, 2012;Radtke et al, 2015;Teicher et al, 2012;Weder et al, 2014), suggesting a direct effect of maltreatment on psychopathologic variables as depression. Meanwhile, in our previous research, we found that internalized symptoms (depression, hopelessness, low self-esteem) was associated with lower meaning in life (Huguelet et al, 2016). Hence, we tested a model in which the effect of child maltreatment was mediated by psychological symptoms.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…epigenetic modifications, explain a part of the increased risk of depression of patients with child maltreatment history (Labonte et al, 2012;Radtke et al, 2015;Teicher et al, 2012;Weder et al, 2014), suggesting a direct effect of maltreatment on psychopathologic variables as depression. Meanwhile, in our previous research, we found that internalized symptoms (depression, hopelessness, low self-esteem) was associated with lower meaning in life (Huguelet et al, 2016). Hence, we tested a model in which the effect of child maltreatment was mediated by psychological symptoms.…”
Section: Introductionmentioning
confidence: 80%
“…This study showed that suffering from a chronic mental condition was associated with reduced meaning in life and impaired values. Moreover, level of depression and hopelessness was associated with lower meaning in life (Huguelet et al, 2016). In this perspective, one might think that it exists an association between child maltreatment and meaning in life, appearing in a multitude of persistent psychiatric disorders, and limiting the potential of recovery in these subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mental health, recovery is understood as a process of personal growth that involves hope, a sense of personal identity, leading a life of meaning and assuming responsibilities 38. The loss of identity and social roles is observed from the very first psychotic episodes 26.…”
Section: Discussionmentioning
confidence: 99%
“…As in the previous analysis, a weighted stepwise linear regression was performed between the z-values of natural logarithm of binding (in this case V T / f P ) for each region and the z-values of three predictors: somatic, motoric and psychic anxiety component scores. As the scales for the predictors were different, we performed the commonly used (Huguelet et al, 2016) z-value standardization in order to ensure that the contributions of the variables to the analysis will be same. The natural logarithm of the outcome measure was applied to improve model fitting as the residuals become closer to normal distribution when this transformation is applied.…”
Section: Methodsmentioning
confidence: 99%